A novel mechanical simulator for cannulation and sphincterotomy after Billroth II or Roux-en-Y reconstruction - Frimberger, Eckart; Abdelhafez, Mohamed; Schmid, Roland M.; von Delius, Stefan (Endoscopy International Open, 2016)
Introduction: In patients with Billroth II (B II) or Roux-en-Y anatomy, endoscopic retrograde cholangiopancreatography (ERCP) is demanding. Here, we describe a novel simulator with simulated fluoroscopy for cannulation and sphincterotomy training in such situations.Methods: A custom-made simulation system was built based upon a common chassis of a series of previously described ERCP simulators. The papilla is made out of organic material and can be cut by high frequency current. The advancement of guidewires and other instruments within transparent mock bile ducts can be viewed in the window of the simulator without the need for fluoroscopy. The ERCP B II/Roux-en-Y simulation system was first evaluated during an ERCP course.Results: There were no technical problems related to the novel simulator during the course. After sphincterotomy, the organic papillae could easily be exchanged within a few seconds. Overall, the novel B II/Roux-en-Y simulator achieved favorable results by trainees and expert endoscopists in all categories assessed.Conclusions: The new B II/Roux-en-Y mechanical simulator is simple and practicable. A first evaluation during an ERCP course showed promising results.